Do Smokers With Respiratory Symptoms but Preserved Lung Function Have a COPD-like Disease?. Issue 6 (November 2016) - Nicholson, Thomas; Zappetti, Dana
Abstract : Synopsis: There are a subset of smokers with preserved lung function who have respiratory symptoms of cough, sputum production, and shortness of breath. These "symptomatic smokers" have exacerbations, decreased exercise tolerance, and airway thickening on imaging, which suggest COPD despite preserved lung function. Source: Woodruff P, Barr R, Bleecker E, et al. Clinical significance of symptoms in smokers with preserved pulmonary function. N Engl J Med . 2016;374:1811–1821.